ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA DAN WORDS OF MOUTH (WOM) PROGRAM PASCASARJANA UNIVERSITAS RIAU PEKANBARU - Sayandra, Recky Riandika; Zulkarnain, Zulkarnain; Samsir, Samsir (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the influence of service quality factors in theGraduate Program of Universitas Riau on student satisfaction and tendency ofwords of mouth among students of Graduate Program of Universitas Riau.Analysis of data influence between research variables using structural equationmodeling (SEM) approach. SEM is a multivariate analysis used to analyzerelationships among variables. One of the software that can be used is IBM SPSSAmos Version 21. Amos was chosen because of the ease in using graphic interface(Amos Graphic) to describe the structural model. Data were obtained from 139respondents by filling out questionnaires. SEM model after experiencing severalstages and modifications have met the criteria of goodness of fit with the value ofeach index are: (a) chi-square= 34,852; (b) cmin/df= 1,452; (c) probabilitas=0,071; (d) GFI= 0,957; (e) AGFI= 0,905; (f) CFI= 0,977; (g) TLI= 0,956; dan(h) RMSEA= 0,057. By looking at the value of iritical, ratio regression weightmore than 1.65 and p-value <0,05, it can be concluded that the service qualityfactor has a significant effect on the student satisfaction and on the factor ofwords of mouth, and also the student satisfaction factor also influence the factorof words of mouth. Furthermore Effect total influence of variable Quality ofservice to student satisfaction variable = 0,808 (80,8%) and to variable of Wordsof mouth = 0,403 (40,3%). While the total effect of Student Satisfaction variableto variable Words of mouth = 0,396 (39,6%). Then the direct influence of variableQuality of service to variable Words of mouth = 0,083 (8,3%) and indirectinfluence of variable Quality of service to variable of Words of mouth = 0,320(32%).